Progressive failure mechanism and stability assessment of high-steep dangerous rock mass: A case study of Heicao dangerous rock mass - Wu Yi; Yihua Dong; Xiaohu Huang; Tianzuo Wang; Yonghuang Deng; Zhengyu Wang (PLoS ONE, 2025)
Western Hubei Province, China, lies in the transition zone between the second and third topographic steps of China’s terrain ladder system. Influenced by the deep incision of the Yangtze River and its tributaries, numerous high-steep slopes have been widely developed in this region.This study focuses on the Heicao dangerous rock mass in Xingshan County, Hubei Province. Through field investigations and Unmanned Aerial Vehicle (UAV) photogrammetry, a discrete element numerical model was developed to investigate the progressive failure mechanisms of high-steep dangerous rock masses under varying lengths of the main structural plane.This study will contribute to future prevention and control of such hazardous rock disasters.The principal conclusions are as follows: (1) The failure surface of the Heicao rock mass exhibits composite form,with the upper section displaying a polyline geometry and the lower section approximating an arc-shaped profile. (2) The main structural plane length significantly affects both the damage extent and propagation velocity in the upper rock mass. (3) Dangerous rock mass instability is jointly influenced by the basal rock mass and the overlying rock mass. Under gravity, progressive failure of the basal rock mass triggers crack development and anti-sliding force attenuation, while main structural plane propagation exacerbates damage. Ultimately, rock bridge shearing and crack coalescence lead to the formation of a progressively penetrating failure surface, resulting in global instability. (4) The results of this study have important theoretical and practical implications for future geological disaster assessment and prevention. In particular, the effective protection of the basement rock mass is the key factor to prevent the formation of dangerous rock mass disasters.